The Temptation Of Magic: Empyreal # 1 - Scott, Megan (New York : Harper, an imprint of HarperCollinsPublishers, 2024)
"He was an Empyreal, her greatest threat, her greatest fascination. Everything she'd been warned against. And yet she wanted him, still. As an Empyreal, Nicole has the ability to kill any deadly supernatural. But if her power ever awakened, the Wake-the organisation that governs supernaturals-would force her to be their loyal huntress. Or kill her, like they did her mother. To stay safe, Nicole hides in a small university town, convinced the mythological art collection at a local manor contains a final message from her mother. But before she can study it, Kyan McCarter, the Wake's most skilled Empyreal, arrives on his own hunt. When they discover his prey has stolen a painting for leverage, they're forced to work together. As the creature threatens to expose Nicole's powers, her tenuous alliance with Kyan threatens her heart. If her true identity is revealed, Kyan will hunt her next. No one disobeys The Wake and survives. Especially when the art they're seeking unveils a conspiracy that would change the lives of creatures and humans forever... But Nicole may only be able to resist one: her wicked impulses, or a love that could repaint their world. And after a life of hiding her true nature, who could resist the temptation of magic"--.
new ya book 2025 spring.
Keywords: Families -- Fiction; Enemies -- Fiction; Magic -- Fiction; Secrecy -- Fiction; Paranormal fiction; Novels; Romance fiction; Fantasy fiction; Young adult fiction